THE RANGE OF VISUAL AIDS AVAILABLE TO THE LANGUAGE TEACHER, AND HOW THEY CAN BE USED IN THE CLASSROOM, MENTIONING THEIR SUITABILITY FOR DIFFERENT LEARNERS - Gauxar Serikbaevna Xaldarchaeva (Galaxy International Interdisciplinary Research Journal, 2022)
In this article Information is provided about best methods,techniques and visual aids in conducting lessons. Visual helps moreover assist us show clearly and easily, without complications or digressions. There are some useful teaching aids, which are implemented in the teaching process such as pictures, timeliness charts and graphs, flashcards, gap fills and realia.